2013
DOI: 10.2478/v10136-012-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin attenuates testicular damage, germ cell death and oxidative stress in streptozotocin induced diabetic rats: naringenin prevents diabetic rat testicular damage

Abstract: The aim of this study was to investigate the protective effect of naringenin on oxidative stress, on proinflammatorycytokines like TGF-β1, IL-1β and on programmed cell death in the testicular damage resultingfrom streptozotocin (STZ) induced diabetes in rats. Diabetes was induced by a single intraperitoneal injectionof STZ (50 mg/kg), and the rats were treated with naringenin (5 mg/kg and 10 mg/kg) administered oncea day orally for 10 weeks, starting 3 days after the STZ injection. At the end of the study, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
(41 reference statements)
3
15
0
Order By: Relevance
“…Among antioxidant components used for male reproductive systems, there is an evidence that naringenin, a well‐known flavonoid, has a considerable influence on the health of testicular cells and can act as a radical scavenger, an immunity system modulator, and an anti‐inflammatory factor . Roy et al demonstrated that narigenin can modulate the levels of ROS and improves diabetes‐induced testicular dysfunction in diabetic rats . Therefore, in this study, we analyzed ROS formation during SSCs culture in 2D and 3D groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among antioxidant components used for male reproductive systems, there is an evidence that naringenin, a well‐known flavonoid, has a considerable influence on the health of testicular cells and can act as a radical scavenger, an immunity system modulator, and an anti‐inflammatory factor . Roy et al demonstrated that narigenin can modulate the levels of ROS and improves diabetes‐induced testicular dysfunction in diabetic rats . Therefore, in this study, we analyzed ROS formation during SSCs culture in 2D and 3D groups.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies demonstrated that naringenin can reduce the side effects of chemotherapeutic drugs, including cisplatin and doxorubicin in testicular and myocardial damages, respectively. Also, naringenin not only reduces the germ cell death but also improves the testicular damage in diabetic rats . Sahin et al found that oral supplementation of naringenin can reduce H 2 O 2 ‐induced testicular damages in rats .…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin, a bitter colourless flavone extract from citrus species (Felgines et al, ; Yáñez et al, ) has been reported to have a wide variety of bioactivity. Naringenin and closely related bioflavonoids are reported to be beneficial for protecting and ameliorating testicular toxicity (Ganaie, ; Jamalan et al, ; Roy, Rahaman, Ahmed, Metya, & Sannigrahi, ; Sahin, Ozkaya, Cuce, Uckun, & Yologlu, ). This has been attributed to their free radical scavenging properties (Ganaie, ; Roy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin and closely related bioflavonoids are reported to be beneficial for protecting and ameliorating testicular toxicity (Ganaie, ; Jamalan et al, ; Roy, Rahaman, Ahmed, Metya, & Sannigrahi, ; Sahin, Ozkaya, Cuce, Uckun, & Yologlu, ). This has been attributed to their free radical scavenging properties (Ganaie, ; Roy et al, ). This study was designed to quantify testicular damage associated with use of HAART and investigated the effect of naringenin on these changes.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is known as a hemosedentary disorder, the continuance of which causes many complications in various organs in the long run (Kawahito et al 2009). Hyperglycemia is one of the characteristics of diabetes, associated with various side effects including sexual disorders, impotence, and infertility (Cudicini et al 1997;Amaral et al 2006;Roy et al 2013;Sisman et al 2014).…”
mentioning
confidence: 99%